Zika virus E protein modulates functions of human brain microvascular endothelial cells and astrocytes: implications on blood-brain barrier properties - Kaur, Guneet; Pant, Pallavi; Bhagat, Reshma; Seth, Pankaj (Frontiers in Cellular Neuroscience, 2023)
Neurotropic viruses can cross the otherwise dynamically regulated blood-brain barrier (BBB) and affect the brain cells. Zika virus (ZIKV) is an enveloped neurotropic Flavivirus known to cause severe neurological complications, such as encephalitis and foetal microcephaly. In the present study, we employed human brain microvascular endothelial cells (hBMECs) and astrocytes derived from human progenitors to establish a physiologically relevant BBB model. We used this model to investigate the effects of ZIKV envelope (E) protein on properties of cells comprising the BBB. E protein is the principal viral protein involved in interaction with host cell surface receptors, facilitating the viral entry. Our findings show that the presence of ZIKV E protein leads to activation of both hBMECs and astrocytes. In hBMECs, we observed a decrease in the expression of crucial endothelial junction proteins such as ZO-1, Occludin and VE-Cadherin, which are vital in establishment and maintenance of the BBB. Consequently, the ZIKV E protein induced changes in BBB integrity and permeability. We also found upregulation of genes involved in leukocyte recruitment along with increased proinflammatory chemokines and cytokines upon exposure to E protein. Additionally, the E protein also led to astrogliosis, evident from the elevated expression of GFAP and Vimentin. Both cell types comprising the BBB exhibited inflammatory response upon exposure to E protein which may influence viral access into the central nervous system (CNS) and subsequent infection of other CNS cells. Overall, our study provides valuable insights into the transient changes that occur at the site of BBB upon ZIKV infection.